Comparative Analysis Of Industrial Shed Between Hot Rolled And Cold Formed Structure Under Wind Load - Rupali Bhanarkar, Raut S.P. , Satish S. Raipure (Drugs and Cell Therapies in Hematology, 2021)
To Make Comparative Analysis Between Hot Rolled Steel (Hrs) And Cold Formed Steel (Crs) Structure Under Wind Load. To Determine The Parameters Such As Node Displacement, Maximum Bending Moment, Maximum Shear Force And Support Reaction Of Shed. Methods: In Present Research, Cold Formed Section Analysis In Accordance With The Guidelines Provided In Is 801:1975 Is Performed On Shed Using Staad-Pro Software. Both The Sheds With Same Geometrical Dimension Are Taken Into Account. The Parameters Which Are Taken Into Account For The Present Study Are Resultant Node Displacement, Maximum Bending Moment, Maximum Shear Force And Maximum Support Reaction. The Behavior Of Cold Formed Steel Is Compared With The Behavior Of Hot Rolled Steel. So Cold Formed Steel Shed Of The Same Structural Configuration As That Of Hot Rolled Steel Shed Is Also Modeled And Analyzed In The Staad-Pro Software. Findings: From The Analysis Of The Analytical Model It Is Observed That The Analytical Results Of Cfs Section Are Comparable With Hrs Section Which Is Used As Purlin In The Industrial Shed. Novelty: As The Cold Formed Steel Is Relatively A New Concept In India, Only Limited Research Has Been Done On Cold Formed Steel.